Gliocova: Predictors of Post-Operative Complications, 30 Day Mortality and Readmission After First Surgical Intervention in Brain Tumour Patients in England Between 2013-2018. (1st October 2022) - Mauricaite, Radvile; Le Calvez, Kerlann; Brodbelt, Andrew; Bottle, Alex; Gregory, Jonathan; Booth, Thomas; Williams, Matt
Abstract: AIMS: The Gliocova dataset uses linked English national cancer data on all 51, 775 adult primary brain tumour patients diagnosed between 2013-2018. Here we investigate patient safety and post-operative complications after first surgical intervention. METHOD: We identified patients undergoing first surgical intervention (surgical debulking or biopsy) and used a modified Delphi approach to identify diagnosis codes indicating potential post-surgical complications. We calculated Elixhauer Comorbidity Index (ECI) weights based on our data and developed regression models to link patient characteristics and ECI with 30-day mortality, readmission and chance of complication. RESULTS: 29, 258 out of 51, 775 patients underwent a surgical intervention (28, 173 surgical debulking; and 1, 207 biopsy). 11, 959 (40.9%) patients had at least one comorbidity during first intervention admission. In hospital mortality was 0.99% (N = 289), 30-day mortality was 2.3% (N = 677) and 30-day readmission was 12.7% (N = 3, 725). 13, 137 patients (44.9%) had at least one complication code from our defined list, either during their first surgical intervention or during a 30-day readmission. Predictors of 30-day mortality, readmission, and risk of complications included age, ECI score, number of complications, type of intervention (biopsy vs surgical debulking), income quintile, and tumour type (i.e., Glioblastoma versus other types of brain tumours). CONCLUSION: To our knowledge this is the first study in England to assess post-surgical complications in a large brain tumour patient cohort. Our further work will focus on variation in outcomes between different centres/ centre volumes/ regions and the cost of complications. More information: https://blogs.imperial.ac.uk/gliocova/about-gliocova/ .